Green transformational leadership and environmental performance in small and medium enterprises. Issue 1 (31st December 2022) - Sun, Xiaomei; El Askary, Ahmad; Meo, Muhammad Saeed; Zafar, Noor ul Ain; Hussain, Babar
Abstract: This study examines the nexus between green transformational leadership (GTL) and environmental performance (EP), considering the mediating role of green human resource management (GHRM) and green innovation (GI). Besides, we also find the moderating effects of environmental values (EV) between GTL and EP. This study collected data from 110 respondents using a survey questionnaire from small and medium enterprises and employed structural equation modeling. The findings confirm a positive and significant effect of GTL on EP. Furthermore, mediation analysis confirms that GHRM and GI positively mediate between GTL and EP. Moreover, it is also confirmed from structural equation modelling that EV play moderating role between GTL and EP. These results offer valuable recommendations for all stakeholders.